find an equation of the tangent line to the graph of y = (ln x)^2, at x = 3
2 answers
the 1st derivative is the slope of the tangent line
y = ln² ( x )
Put x = 3 into the equation y = ln² ( x )
y ( 3 ) = ln² ( 3 )
y´( x ) = dy / dx = 2 ln ( x ) / x
Slope:
m ( x ) = y´( x ) = 2 ln ( x ) / x
Slope of y = ln² ( x ) at x = 3
m = y´( 3 ) = 2 ln ( 3 ) / 3
Equation of the line y = m x + b , for slope m = 2 ln ( 3 ) / 3, passing [ 3 , ln² ( 3 ) ]:
y = m x + b
ln² ( 3 ) = [ 2 ln ( 3 ) / 3 ] ∙ 3 + b
ln² ( 3 ) = 2 ln ( 3 ) + b
ln² ( 3 ) - 2 ln ( 3 ) = b
b = ln² ( 3 ) - 2 ln ( 3 )
y = m x + b
y = [ 2 ln ( 3 ) / 3 ] ∙ x + ln² ( 3 ) - 2 ln ( 3 )
Tangent line to y = ln² ( x ) at x = 3:
y = 2 x ∙ ln ( 3 ) / 3 + ln² ( 3 ) - 2 ln ( 3 )
Put x = 3 into the equation y = ln² ( x )
y ( 3 ) = ln² ( 3 )
y´( x ) = dy / dx = 2 ln ( x ) / x
Slope:
m ( x ) = y´( x ) = 2 ln ( x ) / x
Slope of y = ln² ( x ) at x = 3
m = y´( 3 ) = 2 ln ( 3 ) / 3
Equation of the line y = m x + b , for slope m = 2 ln ( 3 ) / 3, passing [ 3 , ln² ( 3 ) ]:
y = m x + b
ln² ( 3 ) = [ 2 ln ( 3 ) / 3 ] ∙ 3 + b
ln² ( 3 ) = 2 ln ( 3 ) + b
ln² ( 3 ) - 2 ln ( 3 ) = b
b = ln² ( 3 ) - 2 ln ( 3 )
y = m x + b
y = [ 2 ln ( 3 ) / 3 ] ∙ x + ln² ( 3 ) - 2 ln ( 3 )
Tangent line to y = ln² ( x ) at x = 3:
y = 2 x ∙ ln ( 3 ) / 3 + ln² ( 3 ) - 2 ln ( 3 )